Performance of cementitious matrices incorporating concrete floor polishing sludge waste - Silva, Lorena Araujo; Nahime, Bacus de Oliveira; Felipe, Alexsandro dos Santos; Elias, Carlos Nelson; Carmo, Devaney Ribeiro do [UNESP]; Lima, Elton Carvalho de; Santos, Igor Soares dos; Lima, Karen Lopes; Istuque, Danilo [UNESP] (Elsevier B.V., 2020)
The objective of this work is to analyze of reusing concrete floor polishing waste (CFPW) as an additional material to cementitious compounds, reducing at the same time both the consumption of Portland cement and the environmental problems. Mortars and pastes were produced with CFPW additions (4% -mass up to 12%mass) and were characterized in terms of mechanical properties, chemical composition, and thermal analysis. The results of the thermal analysis showed that the moisture carbonation increased as the CFPW %mass increased. The results of the mechanical compression tests showed that the addition of CFPW increases the compressive strength of mortars. The conclusion is that adding CFPW to cementitious compound is feasible in order to reduce the consumption of Portland cement and preserve the environment. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Concrete polishing waste; Cement composites; Sustainability; Microstructural characterization